2012
DOI: 10.2147/ijn.s33120
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effect of particle size and coating type on the blood kinetics of superparamagnetic iron oxide nanoparticles

Abstract: Purpose: Magnetic resonance imaging (MRI), one of the most powerful imaging techniques available, usually requires the use of an on-demand designed contrast agent to fully exploit its potential. The blood kinetics of the contrast agent represent an important factor that needs to be considered depending on the objective of the medical examination. For particulate contrast agents, such as superparamagnetic iron oxide nanoparticles (SPIOs), the key parameters are particle size and characteristics of the coating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Also, such factors as biodistribution and pharmacokinetics of IONP after injection can play an important role in understanding the toxic effects of IONP in vivo. For example, decrease in hydrodynamic size of nanoparticles may significantly increase the blood half‐life time and biodistribution of IONP, thus altering their toxic effects on different organs . As previously was shown in our works, bovine serum albumin (BSA)–coated IONP can be used for glioma visualization and drug delivery of anticancer therapeutics.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Also, such factors as biodistribution and pharmacokinetics of IONP after injection can play an important role in understanding the toxic effects of IONP in vivo. For example, decrease in hydrodynamic size of nanoparticles may significantly increase the blood half‐life time and biodistribution of IONP, thus altering their toxic effects on different organs . As previously was shown in our works, bovine serum albumin (BSA)–coated IONP can be used for glioma visualization and drug delivery of anticancer therapeutics.…”
Section: Introductionmentioning
confidence: 52%
“…For example, decrease in hydrodynamic size of nanoparticles may significantly increase the blood half-life time and biodistribution of IONP, thus altering their toxic effects on different organs. [8] As previously was shown in our works, [9] bovine serum albumin (BSA)-coated IONP can be used for glioma visualization and drug delivery of anticancer therapeutics. Also, it was shown that a decrease in the size of nanoparticles and polyethylene glycol (PEG)coating dramatically increase their ability to visualize rat glioblastoma in vivo and aggregation stability after doxorubicin sorption.…”
Section: Introductionmentioning
confidence: 75%
“…A recent study has clearly shown the decrease of the blood half-life of IONPs from 50 to 3 minutes by increasing their hydrodynamic size from 20 to 85nm. 135 As shown in Fig. 6, IONPs with d H > 100nm quickly accumulate in the liver and spleen through macrophage phagocytosis and entrapment in liver and spleen sinusoids (§2.1.2).…”
Section: Ionps Pharmacokineticsmentioning
confidence: 89%
“…In agreement with relaxation theory, it could be shown that R 1 linearly increases with MLNP concentration but the relaxivity is mostly determined by the size of the magnetite. A smaller size of paramagnetic particles also increases the R 1 relaxivity while R 2 * relaxivity increases with particle size [35]. Given the limited SNR and readout bandwidth provided by a clinical scanner, this was also the reason why we focused on T 1 effects rather than on T 2 * effects in the current investigations.…”
Section: Discussionmentioning
confidence: 99%